POSSIBILITIES OF OPTIMALIZATION OF PUBLIC SOURCES SPENT ON TRANSPORT SERVICE - Miloš Poliak (Perner’s Contacts, 2011)
The goal of this paper is to present the possibilities for optimalization of public financial sources for provision of public transport. This paper proposes to cancel financing of operations and public financial sources on financing of transport service. The transport service has to be depended on transportation flow in region.